Designing an Optimal Education and Training Model for Relationship Managers in the Digital Era - Hidayat, Dayu Nur; Restiandi, Andri; Sukresna, I Made (LifeSciFi, 2025)
The development of digital technology and changes in consumer behavior have encouraged the banking sector, including Bank Rakyat Indonesia (BRI), to adapt by improving the quality of human resources (HR In this context, it is important to design an optimal education and training model for BRI employees, especially RM Briguna, to be able to compete in the digital era. This study aims to evaluate the education and training needs of BRI Briguna RM in the digital era and and design a model that aligns with the specific characteristics and needs of workers, particularly in the eastern region of Indonesia. The method used in this study is a qualitative approach through literature studies, which includes an analysis of various education and training models applied in the banking sector, as well as a review of best practices in HR development. The results of the study indicate that effective training models include competency-based training, on-the-job training, e-learning, blended learning, and gamification. Each model has advantages and limitations that need to be considered in its design. Evaluation of existing training programs indicates the need for adjustments to the curriculum and methods to ensure relevance to industry needs and current technological developments. The optimal education and training model must be flexible, innovative, and in accordance with the specific needs of employees. Investment in HR development and partnerships with educational institutions will be the key to BRI's success in facing challenges in the digital era. By implementing the right model, BRI can build a competent and adaptive workforce, especially RM Briguna in the eastern region of Indonesia, ready to contribute to the company's progress.